Identification of Aedes sp. Mosquito Larvae in Ovitrap in Gunung Kelua Village, Samarinda Ulu District, Samarinda, East Kalimantan: Identifikasi Larva Nyamuk Aedes sp. pada Ovitrap di Kelurahan Gunung Kelua, Kecamatan Samarinda Ulu, Samarinda, Kalimantan Timur - Nova, Dewa Made Rama; Pratiwi, Melynda Dyah; Qhuzairi, Muhammad Rezwan; Sarita, Nadia Rahma; Mapalidara , Alfina; Zahrah, Asma’ Thufailah; Bahar, Gita Wahyuni; Sinaga, Panuturi Ratih Elizabeth Thresna; Riananda , Meidya Rizqi; Paramita, Swandari (B-Creta Publisher, 2025)
Dengue Hemorrhagic Fever (DHF) poses significant public health concerns in Indonesia, primarily transmitted through Aedes aegypti and Aedes albopictus mosquitoes. Between January-November 2024, 70 DHF cases (average 6/month) were reported at Puskesmas Juanda that indicates the necessity for targeted interventions, such as ovitrap usage, to control dengue transmission in vulnerable areas. This cross-sectional observational study aimed to identify Aedes sp. larvae in ovitraps in Gunung Kelua, Samarinda. The data were obtained from primary data by employing 40 ovitraps indoors and outdoors, picked on day-7 then examined under the microscope, and the secondary data from the 2024 DHF case reports in Puskesmas Juanda. The results showed that 73 (85.88%) Aedes sp. larvae in DHF patients’houses and 12 (14.12%) in non-DHF houses, predominantly in RT 17. Larvae were mostly found outdoors. No Aedes sp. eggs or non-Aedes larvae were detected. The study concludes that a total of 73 (85.88%) Aedes sp. larvae were found in the homes of dengue hemorrhagic fever (DHF) patients, 12 (14.12%) Aedes sp. larvae were discovered in non-DHF patients' homes. The highest number of Aedes sp. larvae in both DHF and non-DHF patients' homes were in RT 17. No Aedes sp. eggs were found in ovitraps. No eggs or larvae of other mosquito species besides Aedes sp. were detected.